ANALISIS DAYA DUKUNG EKOWISATA HUTAN PINUS GLAGALINGGAH KECAMATAN KINTAMANI KABUPATEN BANGLI PROVINSI BALI - Widyartha, Made Maha; Adnyana, I Wayan Sandi; Astarini, Ida Ayu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024)DO - 10.24843/EJES.2024.v18.i02.p09, 2024)
Glagalinggah Pine Forest Ecotourism is a tourist destination with its own uniqueness and characteristics in Kintamani District. The purpose of this study was to determine the ecological carrying capacity in Glagalinggah Pine Forest Ecotourism. The method used is the Cifuentes method. The calculation of carrying capacity is based on the vegetation factor that currently exists in Glagalinggah Pine Forest. The Shanon Wiener Biodiversity Index (H`) for vegetation was obtained at 0.81, which means that the diversity in the area is relatively low because there are only 3 dominant species, namely pine, puspa and kacretan. The results of the environmental carrying capacity assessment obtained environmental carrying capacity values, namely physical carrying capacity of 4,773 people/day, real carrying capacity of 649 people/day, and effective carrying capacity of 568 people/day. The level of perception of tourists and managers has a good number of scores. Currently, the number of tourists entering the Glagalinggah Pine Forest is 30 people/day, which is still below the effective carrying capacity threshold, so that tourist visits can still be increased while maintaining the sustainability of the forest. Keywords: Ecotourism; vegetation structure; perception; carrying capacity